PROFESSIONAL TRAINING OF TEACHING STAFF - Sokhiba Ibragimovna Mirkhayitova; Bakhtiyor Umidovich Aminov; Maftunabonu Erkinova (Galaxy International Interdisciplinary Research Journal, 2023)
Design is increasingly used as a specific type of pedagogical reality, including solving the problems of humanization of Education. In the educational space, project activities are not an end in themselves. It is always subject to pedagogical goals and acts as a means of achieving. The article will consider the specifics of innovative activities, features of the implementation of pedagogical project and innovations. Based on the analysis of the history and modernity of philosophical and psychological-pedagogical approaches, a systematic pedagogical project of professional training of specialists was founded and revealed.